RESEARCH AND PRACTICE INTO CULTURAL AWARENESS AND AUTHENTICITY - Sosa, Alma Daniela Otero; Vogt, Terrence Nevin Siders (European Scientific Journal, ESJ, 2014)
Ms. Otero’s bachelor’s thesis researched the issue of cultural awareness. Her advisor (and coauthor of the present article) recommended implementing the task-based approach as put forward by Willis (1998), which provoked an additional theoretical question over the use of a functional approach textbook within a TBL learning cycle. This contribution presents the results from an introductory college class that carried out a project from a standard textbook lesson on health problems, which was expanded into a project on their own health issues. Dramatizations of their own scripting served as the tools through which the students represented their diverse world views on health. The recommendations and treatments they prescribed crystallize their critical thinking within the specific situations